LAWANG SEKEPENG PADA MASYARAKAT KELURAHAN BERENG BENGKEL KECAMATAN SABANGAU PALANGKA RAYA - Norlela Norlela (JURNAL SOCIUS, 2014)
Bereng Bengkel Village is the village that still holds Dayak Ngaju culture. In the other hand, implementation of Lawang Sekepeng in every marriage ceremony in the middle of modern civilization in which this tradition it self is very rarely used. Therefor, the purposes study was the description of Lawang Sekepeng which is still sustained by the community Bereng Bengkel. This study used a qualitative method which aimed was to obtain more complete data, more depth, credible and meaningful so that the research objectives can be achieved. The result found that (1) the concept of Lawang Sekepeng implemented by Dayak Ngaju community at weddings in Bereng Bengkel has slight differences and similarities with the original concept applied by the real Dayak Ngaju community (Kaharingan). Additionally, cultural change in Bereng Bengkel was also motivated by acculturation, assimilation and cultural diffusion.Keywords: Lawang Sekepeng and marriage ceremony